2015
DOI: 10.1016/j.mefs.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional power Doppler indices of ovarian stromal blood flow and serum vascular endothelial growth factor after laparoscopic ovarian drilling in women with polycystic ovary syndrome

Abstract: Objective: To evaluate the effects of laparoscopic ovarian drilling (LOD) on threedimensional (3D) power Doppler indices of ovarian stromal blood flow and serum vascular endothelial growth factor (VEGF) levels in women with polycystic ovary syndrome (PCOS).Design: Prospective controlled study. Setting: Minia University Hospital, Minia, Egypt. Material and methods: 30 clomiphene citrate resistant women with PCOS undergoing LOD and 30 fertile women with normal ovaries were recruited in this study. Hormonal profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The results were in accordance with those recently presented by Al-Rab et al [3], El Behery et al [4] and Elmashad et al [5]. They used similar 3D power Doppler ultrasonography to compare VI, FI and VFI between normal and PCOS group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results were in accordance with those recently presented by Al-Rab et al [3], El Behery et al [4] and Elmashad et al [5]. They used similar 3D power Doppler ultrasonography to compare VI, FI and VFI between normal and PCOS group.…”
Section: Discussionsupporting
confidence: 91%
“…Normal reference value taken for LH was 1.7-13.3 mIU/ml, FSH was 4.5-11.0 mIU/ml, S. estradiol was 40.7-220.4 pg/ml, S. testosterone was 9.0-56.0 ng/dl, DHEAS was 65-524 lg/dl, fasting insulin was 1.1-17.0 lg/ml, fasting glucose was 70-100 mg/dl, HOMA IR was B 2, TSH was 0.39-6.2 lIU/ml and S. prolactin was 2.1-47.6 ng/ml. The Rotterdam's consensus defined the polycystic ovary as having 12 or more follicles, measuring between 2 and 9 mm, and/or an ovarian volume (OV) [ 10 cm 3 . Only one ovary meeting these criteria is sufficient to establish the presence of polycystic ovaries [1].…”
Section: Methodsmentioning
confidence: 99%
“…Among the included studies, Kupesic et al ( 19 ) found a stronger negative correlation (r=−0.67) between follicle stimulating hormone (FSH) and FI in infertile women with normal FSH levels who underwent IVF procedures. Al-Rab et al ( 16 ) found no correlation between FSH and either FI or VI in PCOS patients. Outside this meta-analysis, Wu et al ( 43 ) found strong negative correlations between FSH and ovarian volume, antral follicle count, peak flow velocity and end-diastolic peak velocity in infertile women.…”
Section: Discussionmentioning
confidence: 95%
“…Although many studies have utilized Doppler ultrasonography for women with ovarian dysfunction, the outcomes reported have not always been consistent. For example, a study found no differences ( 15 ), but others have reported significant differences ( 16 , 17 ) in Doppler indices between women with and without PCOS. Some authors have found no correlation between Doppler FI or VI and antral follicles in women with infertility problems ( 15 , 18 ), others have found moderate to high correlations ( 11 , 16 , 19 ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation